Undoing Babel : the Tower of Babel in Anglo-Saxon literature - Major, Tristan (University of Toronto Press, 2018)
Undoing Babel is the first extensive examination of the development of the Babel narrative amongst Anglo-Saxon authors from late antiquity to the eleventh century.